The case of advanced primary squamous carcinoma of vagina in a woman previously treated surgically for cervical dysplasia - Janas, Łukasz; Moszyńska-Zielińska, Małgorzata; Stachowiak, Grzegorz; Stetkiewicz, Tomasz; Nowak, Marek; Rycel, Magdalena; R. Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2012)
The primary cancer of the vagina is a rare neoplasm of the female genital tract. Among all the risk factors for a squamous cell carcinoma of vagina, the human papillomavirus (HPV) infection is mentioned most frequently. Probably for this reason, the likelihood of development of primary cancer of the vagina is higher in women with the history of cervical dysplasia (CIN) and cancer. The article presents the case of a woman who had a hysterectomy with bilateral salpingo-oophorectomy for recurrent CIN. The postoperative pathological investigation confirmed the completeness of the excision. Almost 3.5 years after surgery, the primary cancer of vagina (at the IVA stage according to FIGO) was detected. After ineffective chemotherapy (8 courses) the patient underwent the surgical removal of the upper 2/3 of the vagina, partial resection of the bladder with left ureteric orifice and ureter transplantation, and bilateral systemic pelvic and inguinal lymphadenectomy. Subsequently, the woman was referred for the external beam radiotherapy.